What’s up world with Ian Yee! / Syed Amir Haikal and Nur Ilianis Adnan - Haikal, Syed Amir; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
In the second episode of "What's Up World!'' on 11th November 2021, Ian Yee was invited as a guest speaker by English Club UiTMCPP. He is an editor and executive producer from R.AGE (an investigative and journalism team under THE STAR), nominated TWICE for Peabody Awards in consecutive years and has been selected for the inaugural APAC cohort of the Obama Foundation Leaders Program. This session was hosted by students of UiTMCPP, Syed Amir Haikal and Syaqille. In the session, they explained to the audience about Journalism as well as listing out the challenges that journalism faces. 4 questions were discussed in the session which include what journalism entails, the job description of a journalist, the various types of journalism and the problems faced by journalists. Before the hosts introduced the guest, they played a 1-minute clip of a documentary that R.AGE has done entitled "The Malaysian Drug Trade: Investigating Malaysia's Drug Mule Syndicates". During the interview session, the hosts asked the guest to explain a bit of his background and working experience as a journalist under R.AGE before the 2 main questions were then posed